1970
DOI: 10.2307/2440996
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Comparison of Umbelliferae Subfamilies

Abstract: Serological techniques were employed to compare the three subfamilies Hydrocotyloideae, Saniculoideae, and Apioideae of the Umbelliferae. Data obtained from turbidimetric and double diffusion analyses of seed proteins from thirteen genera demonstrated three distinct serological groupings. These groupings correspond to the three subfamilies. The serological data indicated that one grouping (Apioideae) was more similar to Saniculoideae than to Hydrocotyloideae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The data also indicated that one grouping (Apioideae) was more similar to the Saniculoideae than to the Hydrocotyloideae (Pickering & Fairbrothers, 1970). These groupings essentially correspond to the three subfamilies.…”
Section: Umbellalesmentioning
confidence: 77%
See 1 more Smart Citation
“…The data also indicated that one grouping (Apioideae) was more similar to the Saniculoideae than to the Hydrocotyloideae (Pickering & Fairbrothers, 1970). These groupings essentially correspond to the three subfamilies.…”
Section: Umbellalesmentioning
confidence: 77%
“…Some precipitin reactions are used as an index for determining degree of serological correspondence, which is a summation of the immunological reactions throughout the antigen reaction range. Research has demonstrated that extracts of seeds, pollen, leaves, tubers, and spores of vascular plants can be used, if the required extraction procedures are followed (Fairbrothers, 1969(Fairbrothers, , 1971). Such portions of the single antigenic molecule as are "reprinted" by the specific portion of the antibody molecule are designated "determinant groups," "determinant sites," or "determinants" (Fairbrothers, 1968(Fairbrothers, , 1969(Fairbrothers, , 1970.…”
Section: Macromolecules-systematic Serologymentioning
confidence: 99%